ER, PR, and Her2 immunocytochemistry on cell‐transferred cytologic smears of primary and metastatic breast carcinomas: A Comparison Study With Formalin‐Fixed Cell Blocks and Surgical Biopsies1. Issue 7 (16th July 2012) - Ferguson, Jill; Chamberlain, Pierce; Cramer, Harvey M.; Wu, Howard H.
Abstract The use of formalin‐fixed cell blocks (CBs) for detection of ER, PR, and Her2 status of primary and metastatic breast carcinomas sampled by fine‐needle aspiration (FNA) has been extensively used in clinical practice; however, CBs sometimes lack adequate cellularity even when direct smears are cellular. The aim of this study is to assess the reliability of ER, PR, and Her2 status as demonstrated by immunocytochemical staining (ICC) on alcohol‐fixed direct smears using the cell transfer (CT) technique. FNA cases diagnosed as primary or metastatic breast carcinoma in which the status of ER, PR, and Her2 had been determined either on CB or concurrent biopsy were identified over a period of 18 months. ICC for ER, PR, and Her2 was performed on alcohol‐fixed direct smears using the CT technique. Results were compared with those reported for the corresponding formalin‐fixed tissue. A total of 47 FNA specimens from 46 patients were included in this study. ICC results were excluded from analysis if the CT smear contained fewer than 50 cells. Correlation between the ICC performed on the CT smears and the corresponding CB or biopsy revealed a sensitivity rate for ER, PR, and Her2 of 95%, 90%, and 88%, respectively with a specificity of 100% for all three markers. ICC performed on the FNA smears using the CT technique is a reliable method for assessment of the ER, PR, and Her2 status of breast carcinomas, especially when the direct smears are highly cellular and the CB lacks adequate cellularity. Diagn. Cytopathol. 2013. © 2012 Wiley Periodicals, Inc.